(untitled) (Dissertation Nursing, 2023)
BACKGROUND: Postoperative urinary incontinence is the overall result of urethral sphincter incompetence and modifications in urethral length after radical prostatectomy. Findings for preoperative interventions targeted at preventing post-prostatectomy incontinence include preoperative pelvic floor muscle training (PFMT) and biodfeedback (BFB), which can be managed by nurses in many countries and have been used for decades to speed up continence recovery after surgery. AIM: to determine the effectiveness of preoperative biofeedback (BFB) for post-prostatectomy urinary incontinence compared to pelvic training without BFB, considering the variability between the results of the available studies. METHODS: A systematic review and meta-analysis was conducted, analyzing the indications provided by the literature regarding preoperative biofeedback for preventing urinary incontinence after open radical prostatectomy, in terms of treatment regimens, timing for beginning the sessions, number of contraction and relaxation exercises, and scheduled work at home. Literature search on Pubmed, CINAHL, Cochrane Library, Web of Science, Scopus, EMBASE, and PEdro. RESULTS: Despite only three papers being suitable for metanalysis, our results support BFB over written instructions for continence recovery after both 3 and 6 moths from surgery. Implementing progressive programs with many different muscular exercises and including relaxation are the main recommendations. CONCLUSIONS: Preoperative biofeedback leads to improved urinary continence after 3 and 6 months from radical prostatectomy. Future studies should focus on the characteristics and number of pelvic muscle contractions required during biofeedback in order to maximize effectiveness.